SINGAPOREâ€™S DECISION TO KEEP FIVE POWER DEFENSE ARRANGEMENTS (FPDA) - Fatimah Artayu Fitrazana (HI 16 UMY 011, 2016)
*11 FPDA was established to help the defense of Singapore and Malaysia in 1971. Although it is just a â€œloose consultative forumâ€ but the bodies of FPDA gives the advantage especially to Singapore. In the following years, Singapore also conducts some multilateral security cooperation with others parties and its military armaments also develop to be most sophisticated system. Then writer purposes question about the interest of Singapore to keep Five Power Defence Arrangements (FPDA) and analyzed it by using two concepts which are Rational Actor Model by Graham Allison and Collective Security to bridge the analysis. The data that had been used in this paper are from books, journals and other valid resources. The research is based on library research which is used the secondary data.